2013
DOI: 10.1002/ls.1231
|View full text |Cite
|
Sign up to set email alerts
|

Research of oil film thickness model and surface quality in cold rolling copper foil

Abstract: Rolled copper foil is widely used in high frequency and speed transmission of fine line printed circuit board, because of its high strength, good toughness and high density. In this paper, a theoretical model for copper foil rolling in mixed lubrication regime was developed on the basis of the average volume flow model and asperity flattening model. A more accurate relation for the variation of the lubricant viscosity with pressure and temperature was considered. The cold rolled copper foil experiment was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Surfactants added to the rolling oil form a lubricating film, nanometers thick, 3 by physical or chemical adsorption on the surface of the foil; this inhibits deeper corrosion, and acts as a protective barrier between the metal and its environment. 4 It also has a substantial effect on the conducting properties of the copper foil. 5 In a series of studies, Gagnon 6 showed that fretting corrosion and the severity of wear can usually be reduced by use of lubricants, which reduced contact resistance without having adverse affects.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants added to the rolling oil form a lubricating film, nanometers thick, 3 by physical or chemical adsorption on the surface of the foil; this inhibits deeper corrosion, and acts as a protective barrier between the metal and its environment. 4 It also has a substantial effect on the conducting properties of the copper foil. 5 In a series of studies, Gagnon 6 showed that fretting corrosion and the severity of wear can usually be reduced by use of lubricants, which reduced contact resistance without having adverse affects.…”
Section: Introductionmentioning
confidence: 99%
“…The strip enters the deformation zone and begins to deform when the oil film pressure reaches the strip deformation resistance. The increased behaviour of the oil pressure is indicated by the Reynolds equation [1], as expressed in Equation (5).…”
Section: Oil Film Thickness Formation and Variation Mechanism In The ...mentioning
confidence: 99%
“…Kimura et al [3] and Fujita et al [4] established an estimation model of plate out oil film by experimentally investigating the influences of plate out time, emulsion flow, emulsion concentration, and oil droplet size on plate out oil film formation characteristics. Sun et al [5] and Wu et al [6] developed a theoretical model for mixed lubrication and analysed the effects of surface roughness, rolling speed, rolling reduction, and rolling oil viscosity on oil film thickness in the deformation zone. Fujita et al [7], Wei et al [8], and Zheng et al [9] improved the vibration stability by controlling the lubricity in high speed cold rolling.…”
Section: Introductionmentioning
confidence: 99%
“…As a widely used and important non-ferrous metal material, the lubrication in the production process has been of wide concern in order to produce a rolled copper foil with excellent properties. The application of lubrication technology in the production process of rolled copper foil can effectively reduce the minimum rolling thickness, improve flatness, and decrease energy consumption [3,4]. However, the rolling oil used in lubrication may cause corrosion to the surface of rolled copper foil and then affect the quality of rolled copper foil.…”
Section: Introductionmentioning
confidence: 99%